Analysis and optimization of climbing capability for high-voltage transmission line inspection robots along the route - YANG Zhiyong; WANG Haoyang; XIAO Xi; TIAN Wang (Jixie chuandong)
ObjectiveIn order to enable the inspection robot to pass through the large gradient line smoothly and to improve the climbing ability along the line of the dual-arm wheeled inspection robot, an analysis and optimization was carried out for a dual-armed wheeled inspection robot.MethodsFirst, the force characteristics of the robot during uniform slope climbing were analyzed using a static mechanics model, and a virtual prototype of the robot was established using Adams simulation software to determine its maximum slope-climbing angle. Then, both single-factor and response surface methods were used to analyze the influence of parameters such as the wrapping angle of the walking wheels, the clamping force of the front gripping wheels, and the clamping force of the rear gripping wheels on the robot's maximum slope-climbing angle. Finally, the maximum slope-climbing angle was derived using a linear regression equation, and the optimization results were validated through experiments with a robot prototype.ResultsThe results showed that after optimization, the robot's maximum slope-climbing angle reached 32°, an increase of 92% compared to before optimization. The experimental results indicate that modifying the walking wheel structure and increasing the clamping force can effectively improve the slope-climbing capability of the inspection robot along steep lines.